KETENTUAN NAFKAH KELUARGA DALAM PERSPEKTIF AL-QURAN DAN HADITS - Ansari, Ansari (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2022)
This paper examines the alimony in the family perspective of the Qur'an and hadith contained in surah Al-Baqarah verse 233 and surah Al-Nisaa verse 32, using the library research method, which uses literature, and other legal materials as the main object in studying living in the family. This paper aims to determine whether a wife can work outside the home to provide for the family and how Islam gives the wife the most expansive freedom to work outside the home. A basic need for both husband and wife towards their children and their families is earned. The results of this study show that the wife who works to help the husband meet the livelihood of her legal family mubah (may) with various meanings that the ulama have determined, namely with the husband's permission and indeed solely needed to meet the needs of the family. The need to work for the wife also needs to respect the conditions set by the ulama, namely by avoiding ikhtilat (mixing with men) in work to avoid negative things that may happen.